Disease Patterns in The Baksos Service Community to Improve Efficient ad Better Quality - Soesanto, Danoe (Universitas Wijaya Kusuma Surabaya, 2018)
Recently there are still many community organizations, educational institutions and political organizations conducting free medical service activities, the purpose of that activities varying depend on the organization. The purpose of this study was to described the implementation and outcomes (the number of people served, gender, characteristics of age and what diseases is the most) that activities, Methods of This study was Â a non-experimental research, researcher just observed the subject withoutÂ manipulated or intervention. Result of this study was found the number of women 57.71% and the late adult age to > 65 years old more served during social health service activities, whereas most types of diseases were myalgia 24.09% and hypertension 22.40%. Free medical service activities activity still needed by society but for management of non communicable disease need to reevaluated especially problem of monitoring result of treatment and preventive action which can be done but more cost effective compared with curative action. Further research needed about benefit, the impact and effectiveness of charity medical care activities and the cost comparisonbetween curative efforts and preventive efforts in dealing with hypertension.